(untitled) (Journal of Surgical Sciences, 2020)
Background: Patients with Penetrating Abdominal Injury (PAI) are at risk of harboring life-threatening injuries. Many patients are in need of emergency operative intervention. However, there are some patients who can be safely managed non-operatively. Every patient with an abdominal penetrating trauma should have a thorough clinical examination. Repeating the clinical examination at regular intervals is the cornerstone of selective management, as symptoms and signs that were initially absent may appear later. Objective: To see the efficacy of serial physical examination in patients with penetrating abdominal injury thus avoiding non-therapeutic laparotomy in the overall management of patients. Methods: Convenient and purposive 60 PAI patients admitted in casualty block of Dhaka Medical College & Hospital were selected for selective non operative management (SNOM). On admission the abdominal wound was inspected and neither digital nor direct probing of the wound was attempted. Patients selected for admission had an intravenous line established, a thoracic and abdominal X-ray taken and urine and blood samples were taken. If necessary, a nasogastric tube was inserted. Asymptomatic haemodynamically stable patients were admitted for clinical observation in a single unit during which period the patient was examined by a senior surgeon for clinical re-assessment. Patients were discharged when feeding was normal and if there were clear signs of improvement. Results: Over a 6 month period 60 consecutive patients with penetrating abdominal wound were reviewed. In total 52 patients (86.67%) were managed with clinical re-assessment and discharged without laparotomy. Eight patients (13.33%) underwent laparotomy after observation. Small bowel, liver, mesenteric vessels were most frequently affected. Non-therapeutic laparotomy rate was 0%. After laparotomy the morbidity rates were 62.5% (p = 0.92). One local wound infection occurred without prior laparotomy. Average hospital stay after observation was 2.8 days, after laparotomy 9.8 days. Delayed laparotomy did not increase morbidity or hospitalization. Conclusion: Our experience with penetrating abdominal trauma supports the concept of selective conservatism based on repeated physical examination. In a well-established trauma center this has proven to be highly effective with remarkably low rates of non-therapeutic laparotomies and absence of missed diagnosis of visceral injuries. Journal of Surgical Sciences (2017) Vol. 21 (2): 76-79